Towards the Metaverse: Perspectives for a Harmonious Vision in Schools - Alberto Parola (Pensa MultiMedia, 2023)
In recent years, there has been a growing tendency to discuss the Metaverse, especially following Facebook's decision to rebrand as 'Meta,' a term meaning 'beyond' but also implicitly signalling a change. This concept, while not new, encompasses various aspects such as immersion, cryptocurrencies, limitlessness, synchrony, interoperability, and interactivity. These are evident in the names of metaverses like Sandbox, Decentraland, Roblox, VRChat, Somnium Space, etc., which are linked to video games, viewers, advertising spaces, digital objects, avatars (or digital twins), and more. The approach to the metaverse must be multifaceted, encompassing technological, recreational, scholastic/educational, professional, healthcare, productive, and imaginative aspects. The journey towards adopting diverse approaches has been in progress for some time, yet currently, there seems to be a lull. It is essential to organize and strategize to manage choices and forge connections across various institutional and territorial contexts. This article aims to explore flexible solutions at both the school level and beyond, advocating for an approach that harmonizes the biological and digital 'worlds' as interconnected, balanced, and interdependent entities. With digital technology, students could manage their writings, projects, and artistic endeavours through personal and educational devices, employing both linear (textual) and non-linear (recursive) methods, thus fostering a fully integrated and harmonious identity (holistic approach).